(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2020)
New Cobalt(II) and Nickel(II) metal complexes of 2-aminothiazole (ATZ) and benzoate ion (BEN) ligands were synthesized under microwave irradiation. The empirical formulae and the structure of the complexes have been deduced from CHN analysis, electrical conductance, magnetic moment, electronic (DRS method), Infra Red spectra, TGA analysis, cyclic voltammetry and powder-XRD techniques. The low electrical conductance values indicate that the complexes are non-electrolyte (1:0) type. The electronic spectra and the magnetic moment indicate the structures of the complexes are found to be octahedral geometry. Infra Red spectra illustrate that 2-aminothiazole and benzoate ion is bonded to the metal ion in a monodentate approach. The antifungal activities of ligands and their cobalt(II) and nickel(II) metal complexes were studied aligned with the few microorganisms by agar - well diffusion method at 100,200 and 400 conc. µg/ml concentration. The prepared cobalt(II) and nickel(II) metal complexes show prospective action against the tested fungi as compared to free 2-aminothiazole ligand. The free radical scavenging action of the prepared complexes and the ligand has been resolute by measuring their interface with the stable free radical DPPH. The complexes have larger antioxidant activity as compared to the free ligand. DNA-binding properties have been calculated by fluorescence-emissions method. The obtained results suggest that the complexes powerfully bind to DNA because of metal complexes are well-known to speed up the drug action and the capability of healing agent which can repeatedly be enhanced leading coordination with a metal ion.